2013
DOI: 10.1111/adb.12038
|View full text |Cite
|
Sign up to set email alerts
|

Mephedrone (4-methylmethcathinone) supports intravenous self-administration in Sprague-Dawley and Wistar rats

Abstract: Recreational use of the drug 4-methylmethcathinone (mephedrone; 4-MMC) became increasingly popular in the United Kingdom in recent years, spurred in part by the fact it was not criminalized until April of 2010. Although several fatalities have been associated with consumption of 4-MMC and cautions for recreational users about its addictive potential have appeared on Internet forums, very little information about abuse liability for this drug is available. This study was conducted to determine if 4-MMC serves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
98
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 33 publications
7
98
1
Order By: Relevance
“…These repeated injection studies also used a rectal probe to measure the response at 1 hour intervals so the observed hyperthermia may have resulted from an additive effect of repeated mephedrone injection combined with stress-induced hyperthermia associated with rectal measurement as evident in vehicle control animals (Baumann et al, 2012;Hadlock et al, 2011). The current study therefore used radiotelemetry to measure the temperature response following repeated mephedrone injection and showed it produced hypothermia as reported following a single injection (Aarde et al, 2013;Miller et al, 2012). In the current study, 5,7-DHT administration abolished the hypothermic response to mephedrone.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…These repeated injection studies also used a rectal probe to measure the response at 1 hour intervals so the observed hyperthermia may have resulted from an additive effect of repeated mephedrone injection combined with stress-induced hyperthermia associated with rectal measurement as evident in vehicle control animals (Baumann et al, 2012;Hadlock et al, 2011). The current study therefore used radiotelemetry to measure the temperature response following repeated mephedrone injection and showed it produced hypothermia as reported following a single injection (Aarde et al, 2013;Miller et al, 2012). In the current study, 5,7-DHT administration abolished the hypothermic response to mephedrone.…”
Section: Discussionmentioning
confidence: 84%
“…This is one of only a few studies to use radiotelemetry to obtain a high temporal resolution of changes appropriate for the shortduration responses (Aarde et al, 2013;Miller et al, 2012;Wright et al, 2012). The main findings were as follows; (1) while hyperactivity and increase in extracellular striatal dopamine seen after the first mephedrone injection were similar in magnitude and time course to those seen following the second and third injections, the hypothermia was attenuated with repeated dosing; (2) extracellular striatal 5-HT overflow was more variable but was enhanced when second and third injections were given when compared with the first response; (3) 6-OHDA did not affect hyperactivity but reduced the duration of the hypothermic response; (4) 5,7-DHT administration and 5-HT 1B receptor antagonism attenuated mephedrone-induced hyperactivity; (5) 5,7-DHT administration completely abolished, and 5-HT 1A receptor antagonism attenuated mephedrone-induced hypothermia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mephedrone and MDPV have been shown to be self-administered when given to rats [22,23,26,45,46]. The information currently available about the human effects of these drugs of abuse is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study, methylone did not show an effect of dose on ICSS thresholds even if a trend was observed [25]. Studies have shown that mephedrone and methylone are locomotor stimulants [11,12,[26][27][28].…”
mentioning
confidence: 85%